E-222 How far is too far in stroke thrombectomy? from xl to xs vessel occlusions with radially adjustable stent-retrievers – tigertriever xl and tigertriever 13. (23rd July 2022) - Guenego, A; Lubicz, B
Abstract : Background: A New class of Radially adjustable Stent-retrievers, Tigertriever XL and Tigertriever 13 1, 2 (Rapid Medical, Yoqneam, Israel) are respectively CE-Marked for large, and distal, medium vessel occlusions (DMVO). Despite no randomized data support distal vessels recanalization yet, we report our initial experience with the Tigertriever 13 in DMVO 3 and illustrate it with a case where Tigertriever XL and 13 were needed to obtain a complete recanalization. Methods: We performed a retrospective analysis of all consecutive acute ischemic stroke (AIS) patients with primary or secondary DMVO who underwent mechanical thrombectomy with the Tigertriever 13. Patients' clinical, procedural and angiographic characteristics were reviewed. Results: Between November 2019 and November 2021, 24 DMVO were included (46% female, median age 63 [51–65] years). The overall successful reperfusion rate (mTICI 2b-3) was 88% (21/24) for the dedicated vessel. Follow-up imaging showed a subarachnoid-hemorrhage in 29% of the cases and a parenchymal hematoma in 8% while symptomatic Intracranial hemorrhages did not occurred. At 3 months, 62% of the patients (15/24) had a favorable outcome (mRS 0–2). An example is discussed in figure 1 to 7 . Conclusion: Mechanical thrombectomy for both primary or secondary DMVO seems feasible and as safe as for LVO. Our initial experience using the Tigertriever13 is of special interest as it shows we can potentially significantly expand AIS population that can benefit from mechanical thrombectomy treatment. Disclosures: A. Guenego: None. B. Lubicz: None.